Simulação do controle de posição de um motor de indução trifásico utlizando controle vetorial indireto - Diniz, Eber de Castro (2021)
The principle of vector control of an AC machine enables the dynamic control of AC motors, and induction motors in particular, to a level comparable to that of a DC machine. The vector control of currents and voltages results in control of spatial orientation of the electromagnetic fields in the machine and has led to the term field orientation (BLASCHKE, 1971). Field-oriented control schemes provide significant improvement to the dynamic performance of AC motors. The usual method of induction motor position and torque control, which is becoming an industrial standard (CASADEI et al, 2002), uses the indirect field orientation principle in which the rotor speed is sensed or estimated by rotor position and the slip frequency is added to form the stator impressed frequency. This paper proposes an indirect field-oriented control applied to a small squirrel-cage induction motor using relay feedback method to evaluate the controller parameters, in such a way to show that an AC motor can have similar performance in servo systems compared to DC motors.